MO527: The Active Ingredient in the Nuphar Lutea Plant, 6, 6′: Dihydroxythiobinupharidine (DTBN) Ameliorates Kidney Fibrosis, Inflammation and Anemia in a Mouse Model of Chronic Kidney Disease (CKD). (3rd May 2022) - Khalilia, Jannat; Landau, Daniel; Arazi, Eden; Gopas, Jacob; Segev, Yael
Abstract: BACKGROUND AND AIMS: EPO resistance and iron deficiency in CKD-related anemia are associated with an increase in inflammatory cytokines associated with the innate immune response, such as IL-6, IL-1 and TNF-α. Recently (Bandach et al . Sci Reports 2021) we reported that kidney fibrosis and anemia of CKD can be worsened or relieved when IL1 effects are enhanced or inhibited respectively. The Water lily ( Nuphar lutea ) plant has been widely used as a traditional remedy for the treatment of rheumatism, scars, pain and more. Gopas, Golan-Goldhirsh et al . (Cancer Biology Therapy 2009) extracted an active ingredient from the family of nupharidines: 6, 6′-Dihydroxythiobinupharidine (DTBN), which showed anti-inflammatory properties, mainly through the inhibition of NF-κB. The purpose of this study was to test the effects of DTBN in a mouse model of CKD-associated anemia. METHOD: 8 weeks old male C57BL/6 mice were divided into three groups: control, CKD (induced by adenine diet) and CKD-DTBN. CKD groups were injected with saline-DMSO or 30 µg DTBN, every 2 days and sacrificed after 3 weeks from dietary intervention. RESULTS: Serum urea and kidney TGFβ mRNA were significantly decreased in CKD- DTBN versus CKD. Kidney histology in CKD mice showed macrophage infiltration and renal fibrosis, which was ameliorated in CKD-DTBN. A significant improvement in inflammation indices (blood lymphocytes, kidney and liver IL-6 and p-STAT3, liver CRP), as well as kidney immunoreactive NF-κB and F4\80, which were increased in CKD, were decreased in CKD-DTBN. CKD anemia indices (hemoglobin, hematocrit and red blood cell (RBC) count) significantly improved in CKD-DTBN. Kidney HIF-2α and EPO mRNA were significantly decreased in both uremic groups, but was unchanged in CKD- DTBN versus CKD. However, serum iron and transferrin saturation significantly increased in CKD-DTBN versus CKD. CONCLUSION: Uremic mice treated with DTBN show improvement in kidney fibrosis, inflammation and anemia indices. Thus, DTBN may be a novel therapeutic alternative for CKD and its complications.